The Significance of the Barmen declaration for the Oecumenical church - Kramm, Hans-Herbert (Theology occasional papers, 1943)
Foreword by the Bishop of Chichester.--The confessional synod of the German Evangelical church in Wuppertal-Barmen, from May 29 to 31, 1934.--The Barmen declaration and the church universal, by H.H. Kramm.--The significance of the Barmen declaration for the Oecumenical church, by J.O. Cobham.